2020
DOI: 10.3390/pathogens9100802
|View full text |Cite
|
Sign up to set email alerts
|

First Report on the Finding of Listeria mnocytogenes ST121 Strain in a Dolphin Brain

Abstract: Listeria monocytogenes (Lm) is a ubiquitous bacterium that causes the foodborne illness, listeriosis. Clonal complexes (CC), such as CC121, are overrepresented in the food production industry, and are rarely reported in animals and the environment. Working within a European-wide project, we investigated the routes by which strains are transmitted from environments and animals to food and the food production environment (FPE). In this context, we report, for the first time, the occurrence of a ST121 (CC121) str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…This latter approach compares a large set of genomic data and associates them to specific phenotypic traits, allowing for the identification of markers or indicators of specific phenotypes. The GWAS analysis has been successfully used for identifying Lm genetic determinants involved in biofilm formation ( Lee et al, 2019 ), persistence ( Fritsch et al, 2019 ; Palma et al, 2020 ), and virulence ( Sévellec et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This latter approach compares a large set of genomic data and associates them to specific phenotypic traits, allowing for the identification of markers or indicators of specific phenotypes. The GWAS analysis has been successfully used for identifying Lm genetic determinants involved in biofilm formation ( Lee et al, 2019 ), persistence ( Fritsch et al, 2019 ; Palma et al, 2020 ), and virulence ( Sévellec et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…While nominally commensal in healthy animals, microbes residing on the skin or in the respiratory tract may become pathogenic or more invasive in stressed or immunosuppressed individuals. For example, in harbor porpoises that were immunosuppressed by exposure to heavy metals (Bennett et al 2001), and in recent observation of Listeria mnocytogenes ST121 infection that crossed the blood‐brain barrier in an immunosuppressed dolphin exposed to polychlorinated biphenyl (Sévellec et al 2020). Thus, identification of respiratory microbiome species facilitates follow up on the broad classification of the microbial community with more directed experiments designed to characterize pathogens identified in stranded animals.…”
Section: Discussionmentioning
confidence: 99%
“…Recent application of whole-genome sequencing (WGS) into bacterial molecular characterization provides much data on the relationship of L. monocytogenes from different sources and allows the classification of the strains into evolutionary lines and genetic types [ 15 , 16 , 17 ]. Based on the WGS, the multilocus sequence typing (MLST) approach allows classification of L. monocytogenes into clonal complexes (CCs) and sequence types (STs), which are linked with persistence of the strains in food, food production environments or with a high potential to cause listeriosis [ 18 , 19 , 20 , 21 ]. It has been shown that L. monocytogenes of CC121 classified as serogroup IIa has been often isolated from different food processing plants for several years, which makes them serious problems for the food industry and poses a potential threat for consumers [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the WGS, the multilocus sequence typing (MLST) approach allows classification of L. monocytogenes into clonal complexes (CCs) and sequence types (STs), which are linked with persistence of the strains in food, food production environments or with a high potential to cause listeriosis [ 18 , 19 , 20 , 21 ]. It has been shown that L. monocytogenes of CC121 classified as serogroup IIa has been often isolated from different food processing plants for several years, which makes them serious problems for the food industry and poses a potential threat for consumers [ 20 ]. Other data also suggest that L. monocytogenes IIa serogroup, classified to CC8, CC155, and other clonal complexes, have persistent properties and have been identified in different niches or sources [ 15 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%